Severe allergic reaction following histrelin implant (Supprelin LA) - Sara Donnelly; Dana Shuriff; Steven Stylianos; Jeffrey Zitsman (Elsevier, 2015)
The histrelin implant (Supprelin LA) is an efficacious, safe and well tolerated medication for the treatment of central precocious puberty (CPP). Minor reactions such as bruising, redness, and pain at the implant site have commonly occurred, but only two cases of systemic allergic reaction leading to emergent removal of device have previously been reported. An otherwise healthy eleven-year-old female with CPP and no history of prior supprelin implantation, and a nine-year-old female with CPP and history of two prior supprelin implantations without complications, had a supprelin implant inserted on the same day. Within days of the procedure both presented with severe allergic reaction and underwent removal of the device. A few months after removal, both children had another supprelin implant placed without complications. It was determined that the device was not the cause of the allergic reaction, but rather the dressing material included in the implantation kit that was the offending agent. This report describes two patients with a severe systemic allergic reaction after histrelin implant necessitating urgent implant removal with resolution of allergic symptoms. It was later determined that the allergic reaction was caused by a substance in the self-adhering dressing wrap.